Fewer US Adolescents Playing Football and Public Health: A Review of Measures to Improve Safety and an Analysis of Gaps in the Literature. (September 2021) - Macy, Jonathan T.; Kercher, Kyle; Steinfeldt, Jesse A.; Kawata, Keisuke
Physical activity during adolescence is associated with positive health outcomes, yet only 26% of US middle and high school students report daily physical activity. Moreover, the number of high school students playing a sport is declining, with the largest decline in football. One reason for this decline in playing football may be increased attention to the risk of head injury. For public health, the decline is alarming because football offers a physical activity opportunity for millions of young people every year. In response, efforts have been made to institute measures to enhance the safety of football. The objective of this topical review was to review these measures and the data supporting their effectiveness. We conducted a search of scientific literature supplemented by a web search to identify safety measures. We used the Indiana University library electronic database, PubMed, and web browser searches with specific search terms. In addition to peer-reviewed studies, we searched news stories and reports from sport-related organizations. We summarized the measures and evaluations of effectiveness and categorized the measures by type (game rules, practice guidelines, equipment innovations, strategic initiatives) and target age group (elementary/middle school, high school, college, professional). We found that attempts are being made to improve the safety of football at all levels. However, many measures lack scientific evidence to support their effectiveness. Therefore, researchers need to systematically evaluate safety measures. By implementing evidence-based interventions, we can balance the public health risk of playing football versus the public health risk of continued declines in participation.